Chirality-biased protein expression profile during early stages of bone regeneration - Zeng, Qiang; Zheng, Huimin; Heng, Boon Chin; Yao, Weitong; Yang, Yue; Jiang, Shengjie; Deng, Xuliang (Frontiers in Bioengineering and Biotechnology, 2023)
Chirality is a crucial mechanical cue within the extracellular matrix during tissue repair and regeneration. Despite its key roles in cell behavior and regeneration efficacy, our understanding of chirality-biased protein profile in vivo remains unclear. In this study, we characterized the proteomic profile of proteins extracted from bone defect areas implanted with left-handed and right-handed scaffold matrices during the early healing stage. We identified differentially-expressed proteins between the two groups and detected heterogenic characteristic signatures on day 3 and day 7 time points. Through interaction analysis and in vitro verification, we found that the left-handed chiral scaffold material activated Rho GTPase and Akt1, ultimately leading to M2 polarization of macrophages. By characterizing the protein atlas in the context of bone defect repair and exploring 2 the underlying molecular mechanisms of chirality-mediated polarization differences in macrophages, our study thus improves understanding of the regenerative processes facilitated by chiral materials.